ISOLATION AND CHARACTERIZATION OF LACTIC ACID BACTERIA FROM MANDAI (FERMENTED CEMPEDAK PEEL) IN EAST KALIMANTAN - Jeni Khusnelia; Ervan Johan Wicaksana; Nazarudin Nazarudin; Ilham Falani; Afreni Hamidah; Evita Anggereini (Physics Education Departement, Islamic State University Sulthan Thaha Saifuddin Jambi - Indonesia, 2025)
Mandai is a traditional fermented food from East Kalimantan made from the peel of cempedak (Artocarpus champeden). To the best of our knowledge, this study is the first to report the isolation and characterization of lactic acid bacteria (LAB) from mandai. The fermentation process was carried out for 14 days using MRS Agar medium, resulting in 17 bacterial isolates, consisting of nine Gram-negative and eight Gram-positive isolates. Among them, eight Gram-positive isolates were dominant and exhibited typical LAB characteristics, including acid and gas production from glucose, negative catalase activity, non-motility, growth at 48°C but not at 16°C, and the ability to hydrolyze starch, fat, and casein. During fermentation, the pH decreased from 6.8 to 3.8, confirming active lactic acid production. These findings demonstrate that LAB play a crucial role in generating the characteristic sour taste and improving the quality of mandai. Importantly, the identified LAB isolates have potential as starter cultures to enhance the safety, consistency, and nutritional value of this traditional food.